A LARINGITE NEUROGÉNICA E AS FIBRAS SENSITIVAS - Lima-Rodrigues, Manuel; Valle-Fernandes, Ana; Pinheiro, Joaquim; Neves, Rui; Almeida, Armando (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2005)
.